A 2D SWE meshless model with fictitious water level at dry nodes. Issue 6 (2nd November 2021) - Hsu, Tai-Wen; Liang, Shin-Jye; Wu, Nan-Jing
Abstract : In this study, a two-dimensional shallow-water-equation numerical model is developed for simulating free surface water flows with internal moving wet/dry front boundaries. It is based on the Eulerian aspect and meshless approach. The predictor-corrector process is used for the time marching. The spatial derivatives of physical quantities are computed using the local polynomial approximation with the weighted-least-squares approach. A formula for specifying the fictitious water level, which does not exist physically, at dry nodes is proposed. This is the main novelty of the present study and it significantly reduces computation time compared with the authors' previous work. Four dam break test cases are employed to validate the capability of the present model.